Self‐admission in psychiatry: The ethics. (14th August 2018) - Strand, Mattias; Sjöstrand, Manne
Abstract: Self‐admission to inpatient treatment is a novel approach that aims to increase agency and autonomy for patients with severe psychiatric illness and a history of high utilization of inpatient care. By focusing on brief, preventive hospital admissions in times of increased risk of relapse, self‐admission seeks to reduce the need for prolonged episodes of inpatient treatment. Participants are generally satisfied with the model, which is not surprising given that self‐admission programs allocate a scarce resource—hospital beds—to a select group. However, the patients targeted by these programs are not necessarily those in most need of hospital admission, which may compromise the commonly accepted 'principle of need' in allocation of public healthcare resources. In light of the current lack of consistent evidence of the usefulness and cost‐effectiveness of the model, several aspects need to be further studied in order to guide any large‐scale implementation of self‐admission in psychiatry.